2019
DOI: 10.3390/medicina55060306
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Selected Ion Flow Tube-Mass Spectrometry Technology to Identify Breath Volatile Organic Compounds for the Detection of Head and Neck Squamous Cell Carcinoma: A Pilot Study

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common form of cancer worldwide, with approximately 630,000 new cases diagnosed each year. The development of low-cost and non-invasive tools for the detection of HNSCC using volatile organic compounds (VOCs) in the breath could potentially improve patient care. The aim of this study was to investigate the feasibility of selected ion flow tube mass spectrometry (SIFT-MS) technology to identify breath VOCs for the detection of HNSCC. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The increase in ethanol was also found in head and neck squamous cell carcinoma (HNSCC) patients by Gruber et al, next to 2-propenenitrile and undecane ( 40 ), which discriminated patients from healthy controls and even patients with benign conditions with 77% sensitivity and 90% specificity. Hydrogen cyanide was found to be increased in the breath of HNSCC patients compared to controls using SIFT-MS and allowed discrimination with 91% sensitivity and 76% specificity ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in ethanol was also found in head and neck squamous cell carcinoma (HNSCC) patients by Gruber et al, next to 2-propenenitrile and undecane ( 40 ), which discriminated patients from healthy controls and even patients with benign conditions with 77% sensitivity and 90% specificity. Hydrogen cyanide was found to be increased in the breath of HNSCC patients compared to controls using SIFT-MS and allowed discrimination with 91% sensitivity and 76% specificity ( 52 ).…”
Section: Resultsmentioning
confidence: 99%
“…In oral squamous cell carcinoma, a recent study used EBA and found three compounds (benzaldehyde, 3,7‐dimethylundecane, and butyl acetate) that have a relationship with pathological parameters of these cancers . The methods used for EBA of HNC patients so far include gas chromatography‐mass spectrometry, various nanomaterial‐based sensors and chemical ionization mass spectrometry …”
Section: Exhaled Breath Analysis As a Diagnostic Tool In Head And Necmentioning
confidence: 99%
“…Recent research has analyzed exhaled breath to aid in early detection of HNC . An early attempt to analyze exhaled breath for diagnosis of HNC was conducted by Hakim et al (2011) who used breath gas testing with an artificial nose based on gold nanoparticle sensors.…”
Section: Exhaled Breath Analysis As a Diagnostic Tool In Head And Necmentioning
confidence: 99%
“…Exhaled breath hydrogen and methane have been previously investigated as non-invasive, real-time surrogate markers of the fermentation status of the large bowel 9 , and changes in these exhaled compounds have been linked to colorectal cancer 10 and functional gastrointestinal disorders 11 . Breath volatile organic compounds (VOC) have also recently demonstrated promise as non-invasive biomarkers of HNSCC 12 .…”
Section: Introductionmentioning
confidence: 99%
“…and changes in these exhaled compounds have been linked to colorectal cancer 10 and functional gastrointestinal disorders 11 . Breath volatile organic compounds (VOC) have also recently demonstrated promise as non-invasive biomarkers of HNSCC 12 .…”
mentioning
confidence: 99%